Library jargon : client understanding of technical language used by librarians in reference interviews - Yeo, Meng Choo. (2010)
This study investigated the clients' understanding of technical terms commonly used by librarians during reference interviews, derived from actual librarians' e-mail replies to clients' queries. Two sample groups of client were used for the study. The first group consisted of clientele of the National Reference Library of Singapore. The second group comprised of relatives or acquaintances of the staff from the Library Support Services of the National Library Board of Singapore, who might be potential or actual library clients. Both groups of client were asked to complete a multiplechoice questionnaire, consisting of 20 technical terms, each accompanied with one correct and three incorrect definition options. The findings revealed that the participants were able to define the technical terms correctly three quarter of the time. However, 65% of the participants faced difficulty in defining at least one technical term. The reasons underlying the participants' choices included the appearance of the term in the chosen option and greater familiarity with the selected definition. The methods that were frequently used by the participants to derive the answers were guessing and knowing the meaning in another context. It is recommended that librarians adopt a balanced approach towards the use of technical terms when communicating with the clients. While there is no need to refrain from using technical language totally, librarians should exercise discretion and care when using technical terms.